2020
DOI: 10.1002/cld.896
|View full text |Cite|
|
Sign up to set email alerts
|

Update on Alpha‐1 Antitrypsin Deficiency in Liver Disease

Abstract: Alpha-1-Antitrypsin (A1AT) deficiency (A1ATD) is typically discussed in the context of lung disease as a major cause of panacinar emphysema because of impaired inhibition of neutrophil elastase. SERPINA1, the gene encoding A1AT, has an autosomal recessive inheritance with codominant expression. Large numbers of mutations in the gene are associated with lung disease and a subset with liver disease. Mutations in SERPINA1 causing liver disease do so by the formation of harmful aggregates of mutant A1AT protein wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Shortage of α1-antitrypsin in the lung can be partially overcome by intravenous replacement therapy, while this therapy is not appropriate to people with liver disease. In respective patients, there is emphasis on efforts to prevent progression of related liver injury by reducing of modifiable risk factors (overweight, tobacco, alcohol, non-steroidal anti-inflammatory drugs) or finally liver transplantation that still remains the sole curative option ( Narayanan and Mistry, 2020 ). In cystic fibrosis resulting of mutations in the gene encoding the cystic fibrosis transmembrane conductance regulator (CFTR) the application of Ursodeoxycholic acid (UDCA) is the mainstay of therapy.…”
Section: Therapy Of Hepatic Fibrosismentioning
confidence: 99%
“…Shortage of α1-antitrypsin in the lung can be partially overcome by intravenous replacement therapy, while this therapy is not appropriate to people with liver disease. In respective patients, there is emphasis on efforts to prevent progression of related liver injury by reducing of modifiable risk factors (overweight, tobacco, alcohol, non-steroidal anti-inflammatory drugs) or finally liver transplantation that still remains the sole curative option ( Narayanan and Mistry, 2020 ). In cystic fibrosis resulting of mutations in the gene encoding the cystic fibrosis transmembrane conductance regulator (CFTR) the application of Ursodeoxycholic acid (UDCA) is the mainstay of therapy.…”
Section: Therapy Of Hepatic Fibrosismentioning
confidence: 99%
“…Alpha-1 antitrypsin (A1AT) deficiency is a common inherited metabolic liver disease in the western hemisphere with an estimated incidence of 1:1600 to 1:3500 cases[ 12 ]. SERPINA1 , the gene encoding A1AT, has an AR inheritance with codominant expression[ 13 ]. The liver injury is caused by aggregates of misfolded protein in the hepatocyte whereas the lung injury is caused by unopposed action of neutrophil elastase[ 13 ].…”
Section: Group Amentioning
confidence: 99%
“…SERPINA1 , the gene encoding A1AT, has an AR inheritance with codominant expression[ 13 ]. The liver injury is caused by aggregates of misfolded protein in the hepatocyte whereas the lung injury is caused by unopposed action of neutrophil elastase[ 13 ]. Hence the progression of lung pathology can be prevented with enzyme replacement, but the liver dysfunction does not have a standard medical therapy[ 14 ].…”
Section: Group Amentioning
confidence: 99%
See 1 more Smart Citation
“…In the article by Narayanan and Mistry (2020), 1 the authors have identified an error in the estimated population count reported as 4 million. The corrected sentence should read as follows:…”
mentioning
confidence: 99%